Convergence of the Health Status at the Local Level: Empirical Evidence from Austria - Martin Gächter; Engelbert Theurl (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2010)
In comparisons of the welfare of individuals and socioeconomic aggregates of individuals (regions, states,...) the health status is an important dimension. In the following paper we focus on the question whether the health status between geographical subunits (local communities) converged/diverged in the time period 1969 - 2004 in Austria. We use age standardized mortality rates as indicators for the health status and analyse the convergence/divergence of overall mortality for (i) the whole population, for (ii) females, for (iii) males and for (iv) the gender gap in overall mortality. Convergence/Divergence is studied by applying different concepts of cross-regional inequality (weighted standard deviation, coefficient of variation, Theil- Coefficient of inequality). Various econometric techniques (weighted OLS, Quantile Regression, Kendalls Rank Concordance) are used to test for absolute and conditional beta-convergence in mortality. We find mixed results for the inequality measures applied. Absolute and conditional beta-convergence are confirmed both in weighted OLS as well as in quantile regression estimations, but we also find strong evidence for the existence of convergence clubs in mortality.
Keywords: I1; I3; 330; mortality; convergence; gender; health status; life expectancy; Austria